Palmer Amaranth (Amaranthus palmeri) Suppression with Half Rates of Dicamba and Atrazine with Increasing Sorghum (Sorghum bicolor) Density and Nitrogen Rate - I. B. Cuvaca; R. Currie; A. J. Foster (Kansas Agricultural Experiment Station Research Reports, 2017)
Palmer amaranth (PA) competition can result in severe yield loss in grain sorghum. Increasing sorghum density and nutrient supply could promote early/rapid canopy closure and therefore reduce the amount of light that could otherwise penetrate the canopy and promote PA growth in sorghum. A study was conducted at the Southwest Research-Extension Center near Garden City, KS, to determine if PA could be suppressed with dicamba and atrazine applied as PRE at half rates combined with increasing sorghum density (60,000, 90,000, and 120,000 seeds/a), and nitrogen rate (0, 100, 200 lb/a). Preliminary results indicate that increasing plant density and nitrogen rate did not suppress PA growth. The increase in plant density and nitrogen (N) rate had no affect on reducing PA height, number, and biomass in plots without in-season control (hoeing). In-season control of Palmer amaranth significantly (P<0.01) increased grain yield, sorghum height and number of heads, and was required to maximize yield. These results suggest that increasing plant density within the row does not reduce light penetration into sorghum canopy to suppress PA growth. Therefore, narrow-row planting will be added to the treatment structure to further determine the effect of plant density on suppressing PA in irrigated sorghum production.
Keywords: sorghum; Palmer amaranth; Palmer amaranth suppression; dicamba; half rates; nitrogen rate